Mechanism of Spica Prunellae in Suppressing Proliferation and Stem Cell Properties of Colorectal Cancer Cells Based on Notch Signaling Pathway - TIAN Haoyuan; XIE Yi; FANG Yi; CHENG Ying; LIN Yan; SU Daifeng; WEI Lihui (康复学报)
ObjectiveFrom the perspective of colorectal cancer stem cells，the purpose of this study was to explore the effect and its mechanism of Spica Prunellae on the proliferation and stemness of colorectal cancer cells based on Notch signaling pathway.MethodsColorectal cancer SW480 cells were cultured in vitro. When the cells were in logarithmic growth phase, they were randomly divided into control group, 0.1 mg/mL group, 0.2 mg/mL group and 0.4 mg/mL group. The control group did not receive drug intervention; the other three groups were added with 0.1 mg/mL, 0.2 mg/mL and 0.4 mg/mL Spica Prunellae solution, respectively. Meanwhile, DMSO in each group was supplemented to the same amount. After 24 hours of intervention, the subsequent experiments were performed. The cell growth morphology and density were observed by inverted microscope. The number of viable cells was detected by 0.4% Trypan blue staining and cell survival rate was calculated. The proliferation inhibition rate of colorectal cancer cells was detected using Cell Counting Kit-8 (CCK8) assay. Flow cytometry was used to detect the proportion of stem cells in colorectal cancer cells. The self-renewal ability of colorectal cancer cells was detected by sphere formation assay. Western blot method was used to detect the relative expression of c-Myc, CD44, CD133, SOX2 and Notch pathway-related proteins Notch1 and Hes1 in colorectal cancer cells.ResultsCompared with the control group, the proliferation and viability of colorectal cancer SW480 cells in the 0.1, 0.2, and 0.4 mg/mL groups were significantly inhibited with the increase of Spica Prunellae concentration (P<0.05). The proliferation ability of colorectal cancer SW480 cells significantly decreased with the increase of Spica Prunellae concentration (P<0.05). The proportion of cancer stem cells in colorectal cancer SW480 cells significantly decreased with the increase of Spica Prunellae concentration (P<0.05). The self-renewal ability of colorectal cancer SW480 cells was significantly inhibited with the increase of Spica Prunellae concentration (P<0.05). Compared with the control group, the relative protein expression of c-Myc, CD44, CD133, SOX2, Notch1, and Hes1 in colorectal cancer SW480 cells was significantly down-regulated with the increase of Spica Prunellae concentration in the 0.1, 0.2, and 0.4 mg/mL groups.ConclusionSpica Prunellae can inhibit the proliferation and stem cell properties of colorectal cancer cells, and inhibition of the Notch pathway activation may be one of the important mechanisms.